The Use of Picture in Teaching Degrees of Comparison - Lukman Lukman; Ilham Ilham (Muhammadiyah University of Mataram, 2018)
The objective of this quantitative study is to investigate whether there any influence of using a picture in teaching degree of comparison or not and to know the students’ responses at the second year students of SMP Negeri 9 Mataram in academic year 2014/2015. The population of this study was taken from all the second year students. The writer chose two classes to compare by using the technique of taken sample “cluster random sampling.” The first class as the experimental class (A class) was taught by the degree of comparison through pictures. The second class as a control class ( B class) was taught without pictures. While 34 students of the experimental group and 34 students of the control group. This study used an experimental study with a quantitative method — the data collected procedure by test and questionnaire. The writer gave the pre_test, the treatment, the post_test, and the questionnaire. After collecting and calculating the data, the writer found out that the experimental class gains a high score than the control class. Based on the result, the means scores of A class was 25 while the B class was 16. Moreover it was found that the value of t_test was higher than t_table, where t_test 2, 5 ≤ t_table = 2, 0 (0, 5% or 95%). The finding showed that there any influence of using the picture in teaching comparison degrees. The picture increases students’ responses to learning degree of comparison the class and also given good influence concerning students’ skill in mastering the subject of comparison degrees. It showed by students’ responses of the data from the questionnaire that more than half of students answer yes with percentage was 73%. It means that the picture has a great contribution for students in learning comparison degrees. Therefore, it can be concluded that Ha is accepted and H0 is rejected.